Off-pump versus on-pump coronary artery bypass grafting: a propensity score-matching analysis of safety and long-term results. (14th October 2021) - Saraiva, F A; Cerqueira, R J; Ferreira, A F; Moreira, R; Amorim, M J; Barros, A S; Pinho, P; Lourenco, A P; Leite-Moreira, A F
Abstract: Background: The role and the indications for using off-pump coronary artery bypass surgery (OPCAB), instead of the traditional on-pump (ONCAB), is still to be addressed. Aim: To describe our centre experience and to compare 15-years survival and early safety outcomes between OPCAB and ONCAB. Methods: Single-centre retrospective cohort including 9-years of isolated first CABG (2005–2013). Multi-vessel disease with at least 2 surgical grafts patients were considered and the first 50 surgeries of each surgeon with each technique were excluded to account for the learning curve effect. Emergent surgeries and on-pump beating heart procedures were also excluded. A propensity-score matching (PSM) analysis was performed to balance groups and both survival and early outcomes comparison was done within the matched cohort using Kaplan-Meier or Cox stratified and paired tests, respectively. The median follow-up was 9 years, maximum 15 years. Results: From 3012 multi-vessel patients with at least 2 surgical grafts, 2503 were included at the main analysis: 1487 ONCAB and 1016 OPCAB. ONCAB patients presented more frequently 3-vessels disease and left ventricular dysfunction, but received similar number of grafts than OPCAB, who in turn, received more frequently multiple arterial grafts. The surgical completeness of revascularization (CR) was similar, but hybrid procedures were more frequent in OPCAB raising CR rate in this group. After PSM (646 pairs), both groups were similar regarding pre and peri-operative characteristics. The long-term survival was similar (HR stratified by pair: 1.02 (0.81–1.30), but OPCAB evidenced benefits at early term results including bleeding, postoperative atrial fibrillation and stroke incidence. Conclusion: At our centre, OPCAB performed by experienced surgeons provides rates of complete revascularization and long-term survival similar to ONCAB. In-hospital results favoured OPCAB. FUNDunding Acknowledgement: Type of funding sources: Other. Main funding source(s): Universidade do Porto/FMUP; Social European Fund; FCT-Fundação para a Ciência e a Tecnologia